2016
DOI: 10.1001/jamaoto.2016.1444
|View full text |Cite
|
Sign up to set email alerts
|

Association ofTMTC2With Human Nonsyndromic Sensorineural Hearing Loss

Abstract: IMPORTANCE Sensorineural hearing loss (SNHL) is commonly caused by conditions that affect cochlear structures or the auditory nerve, and the genes identified as causing SNHL to date only explain a fraction of the overall genetic risk for this debilitating disorder. It is likely that other genes and mutations also cause SNHL. OBJECTIVE To identify a candidate gene that causes bilateral, symmetric, progressive SNHL in a large multigeneration family of Northern European descent. DESIGN, SETTING, AND PARTICIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Phenotype characteristics and effective intervention outcomes for S60 and S61 were similar to those previously reported for an unrelated family of Northern European descent who also harbored the TMTC2 rs35725509 variant (Runge et al., ). Objective ECAP measures and speech perception abilities indicated effective stimulation of the auditory system with cochlear implants, and are consistent with postlingual hearing loss onset.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Phenotype characteristics and effective intervention outcomes for S60 and S61 were similar to those previously reported for an unrelated family of Northern European descent who also harbored the TMTC2 rs35725509 variant (Runge et al., ). Objective ECAP measures and speech perception abilities indicated effective stimulation of the auditory system with cochlear implants, and are consistent with postlingual hearing loss onset.…”
Section: Discussionsupporting
confidence: 79%
“…TMTC2 is a gene that, outside this and one other study (Runge et al, 2016), had not been previously implicated in hearing loss. In both cases, a strong association of the rs35725509 variant to the nonsyndromic SNHL phenotype was uncovered.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This connection may extend to hearing loss in patients as well. In parallel with our work recently, a missense mutation (rs35725509; Val136Ile) in the human ortholog TMTC2 was linked to nonsyndromic sensorineural hearing loss both in a 6-generation family and in a cohort of unrelated individuals with SNHL (179 affected vs. 186 matched controls) (19,35). This mutation was also recently identified in another family dyad with hearing loss (35).…”
Section: Discussionsupporting
confidence: 73%
“…These published data also demonstrate that the level of Tmtc4 (both mRNA and protein) in the cochlea is higher than the other 3 isoforms (Tmtc1,2,3), although all 4 are expressed in the cochlea (18). Given the broad expression of all isoforms in the cochlea and the recently published linkage of TMTC2 to hearing loss in humans (19), we also tested whether inactivation of Tmtc4 led to a change in the abundance of other isoforms. As measured by quantitative PCR (qPCR), we found that there was a significant increase in the levels of Tmtc1, Tmtc2, and Tmtc3 mRNA in the cochlea of Tmtc4-KO mice compared with littermate WT controls, suggesting possible shared functions (Supplemental Figure 3).…”
Section: Introductionmentioning
confidence: 93%